Hybrid strengthening of steel-concrete composite beam, part 1: Experimental investigation. (February 2018) - Subhani, Mahbube; Al-Ameri, Riyadh; Kabir, Muhammad Ikramul
ABSTRACT: Due to the partial interaction between steel beam and concrete slab, two neutral axes in a steel-concrete composite beam are formed, sometimes even at low load. As a result, both the soffit of the slab and beam can be in tension if slip is allowed in the composite beam which is a common case for numerous composite beams. While most the previous studies emphasised on the strengthening of the steel beam only, this study investigates the effect of strengthening both the concrete slab and steel beam. To perform this, two commonly used materials, carbon fibre reinforced polymer (CFRP) and steel plates, are implemented in different combination. The arrangements include CFRP on both the slab and beam, steel plate on both concrete and steel, CFRP on concrete and steel beam separately, steel beam on the slab and beam separately and the hybrid technique which is the combination of both CFRP and steel plate. In addition, the techniques are also compared against the beams where almost full interactions are achieved to explore the suitability of the proposed scheme if partial interaction is absent. It is found that the hybrid strengthening can enhance the maximum load carrying capacity, stiffness and ductility of a steel-concrete composite beams when partial interaction is present between the concrete slab and the steel beam. Highlights: Hybrid strengthening of steel-concrete composite beams is proposed. Strengthening of both slab and beam element increase the retrofitting efficiency. Hybrid strengthening can enhance up to 15% of ultimate load carrying capacity. Welded steel plate contributes more on the ultimate load carrying capacity. CFRP contributes more on the ductility of the beam.